Chemical constituents, in vitro anti-inflammatory, antioxidant and hemostatic activities of the n-butanol extract of Hyacinthoides lingulata (Poir.) Rothm. Issue 12 (15th June 2022) - Hanfer, Mourad; Benramdane, Zeyneb; Cheriet, Thamere; Sarri, Djamel; Menad, Ahmed; Mancini, Ines; Seghiri, Ramdane; Ameddah, Souad
Abstract: The phytochemical profile obtained from LC-ESI-MS/MS analysis of the n -butanol extract (BEHL) from the North African endemic plant Hyacinthoides lingulata (Poir.) Rothm. brought about the identification of ten glycosylated derivatives of apigenin and luteolin flavones. For the same plant extract, in vitro anti-inflammatory (hypotonic induced hemolysis and heat induced haemolysis assay) and antioxidant (DPPH and β -Carotene) activities were evaluated observing high inflammatory inhibition by protecting membrane stability of erythrocyte in both heat (84.70 ± 0.24%) and hypotonic induced hemolysis (79.45 ± 0.12%). A remarkable hemostatic effect was also established by measuring the coagulation time (15.95 ± 1.05 s at a dose of 1 mg/mL) of decalcified plasma related to its phytochemical content. It is the first report on combined chemical components and biological evaluation of this specific plant. Graphical Abstract: UF0001